REGRESSION OF PULMONARY HYPERTENSION AFTER CORRECTION OF ABNORMAL PULMONARY VEIN DRAINAGE - Mamatov M.A.; Abrolov H.K.; Akbarkhonov B.A. (Scholar Express Journals, 2024)
The widespread prevalence of cardiovascular diseases accompanied by a rather high mortality rate predetermined the progress and modern trends in the development of cardiac surgery. In this aspect, over the last two decades, remarkable successes have been achieved in the diagnosis and surgical treatment of complex congenital heart defects, and anomalous pulmonary vein drainage can be included to them.
Keywords: pulmonary hypertension; correction of anomalous drainage; pulmonary veins